Peran Kualitas Bukti Audit dalam Meningkatkan Kredibilitas Laporan Keuangan: Literatur Review - Zahrul Tamami; Muhammad Hisyam; Trinandari Prasetya Nugrahanti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the role of audit evidence quality in improving the credibility of financial statements based on the perspective of agency theory, assurance theory, and legitimacy theory. This research employs a literature review approach using the Systematic Literature Review (SLR) method, utilizing secondary data sourced from relevant books and journal articles published between 2017 and 2025. The results of the study indicate that the four dimensions of audit evidence quality, relevance, reliability, timeliness, and sufficiency, play a significant role in enhancing the reliability of the audit process and the credibility of financial statements in the eyes of stakeholders. Relevance is influenced by the type of findings and audit objectives, reliability is determined by objectivity and external sources of evidence, timeliness is related to the appropriate reporting period, while sufficiency depends on the level of risk and complexity of the transaction. High quality evidence reflects the auditor's independence, professionalism, and compliance with standards and codes of ethics, thereby strengthening public trust in the integrity of financial information. Thus, the quality of audit evidence is not only technical, but also an important instrument in maintaining the company's legitimacy and credibility in front of stakeholders